2016
DOI: 10.1021/acschemneuro.6b00091
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multifunctional Compound Camellikaempferoside B Decreases Aβ Production, Interferes with Aβ Aggregation, and Prohibits Aβ-Mediated Neurotoxicity and Neuroinflammation

Abstract: Accumulating evidence suggested that soluble oligomeric β-amyloid protein (Aβ) exerts diverse roles in neuronal cell death, neuroinflammation, oxidative stress, and the eventual dementia associated with Alzheimer's disease (AD). Developing an agent with multiple properties may be a reasonable strategy for the treatment of AD. In this study, we isolated a novel multifunctional compound named camellikaempferoside B (YCF-2) from Fuzhuan brick tea. YCF-2 consists of kaempferol backbone, p-coumaric acid (p-CA) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The TOF-MS/MS spectra of both the compounds showed the loss of A-ring of the flavanolic unit (−126 Da), whereas the loss of the [gallic acid-H 2 O] moiety provided the fragment ion at m/z 305.0673(78). The presence of gallic acid was further confirmed by the fragment ion at m/z 169.0146 (51), which was for compound 15 the base peak of the TOF-MS/MS spectrum ( Figure S4A; [35,37]). A similar fragmentation pathway characterized compound 26, which was tentatively identified as epicatechin gallate, whose TOF-MS/MS spectrum also showed the gallate ion as base peak ( Figure S4B).…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 78%
See 1 more Smart Citation
“…The TOF-MS/MS spectra of both the compounds showed the loss of A-ring of the flavanolic unit (−126 Da), whereas the loss of the [gallic acid-H 2 O] moiety provided the fragment ion at m/z 305.0673(78). The presence of gallic acid was further confirmed by the fragment ion at m/z 169.0146 (51), which was for compound 15 the base peak of the TOF-MS/MS spectrum ( Figure S4A; [35,37]). A similar fragmentation pathway characterized compound 26, which was tentatively identified as epicatechin gallate, whose TOF-MS/MS spectrum also showed the gallate ion as base peak ( Figure S4B).…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 78%
“…Acyl flavonoid glycosides were identified as active ingredients with good Kaempferol coumaroyl glycosides, such as camellikaempferoside B, were reported as a constituent of Fuzhuan brick tea, which is a kind of uniquely microbial fermented tea in China [50]. This compound was found to possess the properties of both kaempferol and p-coumaric acid and significantly inhibit Aβ production by decreasing β-secretase activity [51]. Their biosynthesis is mediated by an acyltransferase, namely CsHCT, that can catalyze the transfer of an acyl group to the donor substrate [52].…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 99%
“…Inhibition of Aβ aggregation may simultaneously alter the conformation of Aβ and reduce Aβ oligomer‐induced cytotoxicity . Our results showed that AOEP2 inhibited Aβ aggregation but did not decrease the oligomer formation.…”
Section: Discussionmentioning
confidence: 62%
“…Compelling evidence has demonstrated that Ab produces toxicity in neurons (73,74) and in glial cells (75,76). These observations have been corroborated in mice and rats (77,78), especially Tg2576 mice, which are a canonical AD experimental model.…”
Section: Signaling Pathways Involved In Mediating the Effects Of Cox-mentioning
confidence: 88%